(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the acceptability and effect of a psychoeducational intervention program on the burden of family caregivers of the older adults. Method: Quasi-experimental study carried out with six caregivers of totally dependente older adults residents in the city of Palmas/TO, in the year 2021. The intervention implemented was the “Program to take care of myself to take care of the other” conducted by telephone support, individually, once per week for five weeks. Care overload was measured by the Zarit Scale, at three moments: pre-intervention and two post-intervention (in the 6th and 10th follow-up sessions). For the analysis, the paired T test was used. Results: A significant difference was identified between the means of burden scores in the pre-intervention (mean=47.33 points) and in the 10th follow-up session (mean=42 points). Regarding acceptability, the caregivers investigated reported satisfaction and usefulness of the intervention program, demonstrating that expectations were exceeded. Conclusion: The psychoeducational intervention showed a decrease in the levels of burden of family caregivers of older adults, indicating the importance of fully carrying out the proposed intervention, since its effect was established over time.